Facilitators of and barriers to the clinical implementation of evidence-based nursing guidelines based on the Consolidated Framework for Implementation Research: A multisite survey. - Qin, Peiwei; Liu, Qiuru; Wang, Haixia; Li, Zeyu; Shi, Junfang; Cui, Qiongfang; Dai, Yaxin; Wu, Xing; Ma, Peifen (International Journal of Nursing Sciences, 2026)
This study aimed to explore the facilitators of and barriers to the clinical translation of evidence-based nursing guidelines. A convergent mixed-methods study design. First, 206 nurses from 12 hospitals were selected as study participants, and the Chinese version of the Organizational Readiness to Change Assessment (ORCA) scale was administered to assess the current readiness for guideline implementation. Subsequently, for the qualitative study, purposive sampling was used to select 15 nurses from the quantitative study sample for semistructured interviews. The framework analysis method was applied to code the transcribed texts using the Consolidated Framework for Implementation Research (CFIR), and thematic analysis was employed to identify facilitators and barriers to guideline implementation. Finally, all facilitating and barrier factors were systematically synthesized, and implementation strategies were matched using the Consolidated Framework for Implementation Research–Expert Recommendations for Implementing Change (CFIR–ERIC) tool. The organizational change readiness score was moderate-to-high (248.77 ± 33.35). The quantitative study identified 25 facilitating factors (such as the scientific rigor of guideline implementation and a positive departmental culture) and 16 barriers (including insufficient resources to address patient awareness or needs and inadequate communication among team members). The qualitative study identified 25 facilitating factors (such as high self-efficacy in evidence-based practice and leadership support) and 11 barriers (such as implementation complexity and resource constraints). From a mixed-methods analysis, the top three barriers were identified as a lack of incentives, insufficient resources, and interdepartmental communication barriers. Based on the CFIR-ERIC mapping, implementation recommendations targeting the main barriers were identified, including tailoring implementation strategies, modifying incentive mechanisms or compensation structures, and establishing communication networks among team members. This study systematically revealed, through a mixed-methods approach, the current status of nurses' readiness to participate in guideline implementation in China, as well as the facilitating factors and barriers. In the future, targeted strategies should be developed based on the identified barriers to promote the sustained implementation of guidelines.